Simulation of Telemetry System for Monitoring Fuel Level Based on SMS Gateway - Yuda Indra Pranata; Muchlas Arkanuddin (Universitas Ahmad Dahlan, 2020)
This study aims to simulate a telemetry system monitoring the level of the fuel level at an SMS-based gas station using an ultrasonic sensor integrated with the Arduino Uno microcontroller. The gas station's fuel tank was simulated using a 5 liter reservoir, while the HC-SR04 ultrasonic sensor was used to detect fuel level. The SIM800L module is used as a sender of information messages about the fuel level at a predetermined condition. This system is equipped with an LCD as a viewer when the data level is read. Based on testing the developed system can function well, shown by the average length of time the process of sending messages from reading the level limit on the tank, until the receipt of messages on mobile phones of 7.6 seconds. While the success rate of reading to the level of fuel level and sending automatic messages on the system reaches 100%.Penelitian ini bertujuan untuk membuat simulasi sistem telemetri pemantauan level ketinggian BBM di SPBU berbasis SMS gateway menggunakan sensor ultrasonik yang diintegrasikan dengan mikrokontroler Arduino Uno. Tangki BBM SPBU disimulasikan menggunakan sebuah tandon berkapasitas 5 liter, sedangkan sensor ultrasonik HC-SR04 digunakan untuk mendeteksi level ketinggian BBM. Modul SIM800L digunakan sebagai pengirim pesan informasi mengenai level ketinggian BBM pada kondisi yang telah ditentukan. Sistem ini dilengkapi dengan LCD sebagai penampil ketika data level terbaca. Berdasarkan pengujian sistem yang dikembangkan dapat berfungsi dengan baik, ditunjukkan oleh rata-rata lamanya waktu proses pengiriman pesan dari pembacaan level limit on tank, hingga diterimanya pesan pada handphone sebesar 7,6 detik. Sedangkan tingkat keberhasilan pembacaan terhadap level ketinggian BBM dan pengiriman pesan otomatis pada sistem tersebut mencapai 100%.